Peran Tokoh Agama dalam Membangun Akhlak Remaja di Desa Lau Buluh Kecamatan Kutabuluh Kabupaten Karo - Nasution, Ahmad Habib; Harahap, Mardian Idris; Alfikri, Muhammad (Medan Resource Center, 2022)
The role of religious leaders in building adolescent morals is very influential, because without realizing it, religious leaders in a village, especially lau buluh village. Religious leaders on one of the ladders as intermediaries can approach teenagers as an extension of our tongue so that we are more respected among teenagers and more listened to. This research is a field research using a qualitative approach. As a field research, this research was conducted in lau buluh village, kuta buluh district, karo regency, north sumatra province, with the research time starting from august to september 2021. Primary data in this study were obtained directly through interviews with informants, namely lau buluh village officials, community and religious leaders, as well as religious affairs office apparatus in kuta buluh sub-district, karo district. As for secondary data in this study obtained through library studies. Data collection techniques in this study used direct or covert observation techniques semi-structured interview techniques, and documentation/literature techniques. The data analysis technique used in this research is the miles and huberman model data analysis, with aktivities in data analysis starting with data collection, data reduction. The result of this research is that the research aims to provide an understanding to the general public that the morals of teenagers are now a question for us, why the chastity of adolescent morals is now different. This is a challenge for perents in educating their children. Because we see many parents who are diligent in worship, but do not emphasize the importance of worship in children. Maybe it’s better for children to control their parents. The most important influence of the damage to adolescent morals is from parents, because parents are the person in charge and the main pillar for a child. In the process of educating children, parents must be patient and gentle and the most importhat thing is to prioritize educating morals first than knowledge. Because morality is more importhat than knowledge.